MSME FINANCIAL LITERACY TRAINING FOR SERANG RAYA UNIVERSITY ALUMNAE - Deni Sunaryo (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2022)
Financial literacy is an important knowledge to improve people's welfare in the future. Some of the fundamental variables of financial literacy include an understanding of inflation, numeration or interest rates, risk diversification and compound interest. Every year, many Alumnae of Serang Raya University become young entrepreneurs who have a better level of education than the previous generation, including knowledge of finance. According to a report from the Central Statistics Agency (BPS) related to Indonesia's Population Projection, it is stated that the population with a vulnerable age of 20-34 years can simply be grouped into millennials and Alumnae are part of millennials. The millennial generation will in time have personal financial responsibilities. They will make important financial decisions that can affect the level of welfare in the future. Keywords : ,,